Comparison of the Prevalence of Human Papillomaviruses among Fertile and Infertile Women in Mashhad, Northeast of Iran - Javanbakht, Aida; Meshkat, Zahra; Khadem Ghaebi, Nayereh; Meshkat, Mojtaba; Ayati Afin, Sedigheh; Javan, Narges; Rostami, Sina (Archives of Medical Laboratory Sciences, 2019)
Background: Human papillomaviruses (HPVs) are the most common viruses which can be sexually transmitted. They can cause different malignancies in asymptomatic women. The association of HPVs with infertility among men and women is controversial. In the current study, the authors compared the frequency of HPVs in fertile and infertile women in the city of Mashhad. Materials and Methods: In the present case-control study, cervical and vaginal smears were collected from infertile and fertile women. HPVs were detected by polymerase chain reaction. Data was analyzed by SPSS v.20 and P-value <0.05 was considered statistically significant. Results: In the current study, 115 infertile women with the mean age of 30.5±5.6 years and 60 fertile women with the mean age of 32.6±9.3 years were included (p=0.07). Among women who were infertile (cases), 121 (52.6%) of 230 smears were positive, while in control group (who were fertile), 50 (41.7%) of 120 smears were positive (p=0.052). Conclusion: Frequency of HPV in both groups was high, which could be due to lack of routine HPV vaccination. HPV can cause placenta abnormality, our infertile women had multiple abortion history and history of abortion had significant differences among infertile and control group. The frequency of HPV had no significant differences between the infertile and control groups.